Systematics, bionomy, and metamorphosis of Coleoptera (Insecta): Papers celebrating the 80th birthday of Cleide Costa - Foreword from the editors - Casari, Sônia A.; Biffi, Gabriel (Papéis Avulsos de Zoologia, 2020)
We present a brief biography of Dr. Cleide Costa, eminent entomologist from Museu de Zoologia da Universidade de São Paulo (MZUSP). She has been dedicating the last six decades to the study of adults and immatures of Coleoptera. Dr. Costa is the pioneer in collecting and rearing immature beetles in Brazil, being responsible for establishing the most extensive Latin American collection of reared immatures Coleoptera. We discuss central aspects of her personal history, as well as career landmarks and achievements. A compilation of taxa introduced to science by her, taxa named in her honor, and a full list of her scientific, educational and cultural production are provided in chronological order. More than a biographical account, this publication is an acknowledgment of Dr. Cleide Costa’s legacy to entomology.